Faktor-faktor yang Mempengaruhi Kebijakan Dividen pada Bank yang Terdaftar di Bursa Efek Indonesia - Henny Ritha -; Tria Anisa - (JEBIM Prima, 2020)
This research is aimed to analyze the effect of profitability, cash ratio, debt to equity ratio, size, and growth on dividend policy in Indonesia Stock Exchange from 2008 to 2013. The sample was selected by using purposive sampling technique. Technique analysis used panel data regression analysis with Microsoft Excel 2010 data processing and Eviews.8. From the results of the panel data processing, the Fixed Effect Model approach is obtained as the best model for estimating panel data regression model. The research proves that partially, profitability and cash ratio have negative and significant impact on dividend policy. Meanwhile, debt to equity ratio, size, and growth did not have any significant impact on dividend policy. An ability of independent variables state the dependent variable 48.78%, meanwhile the remaining 51.22% is influenced by other variables.